Production of Complex Fertilizer by Activating Low-Grade Phosphorites. A Review - Kholiyorova Oghiloy J; Mirzakulov CH. X; Diyarov Kh.D. (Genius Journals, 2023)
In this scientific work, a studying of conducted on obtaining mineral complex fertilizers using methods of thermal enrichment of low-grade phosphorites. Enrichment of lowgrade phosphates Production from non-enriched phosphate raw materials and thermal concentrate has been launched. Technical conditions have been developed for all types of raw materials in Central Kyzylkum. Despite the similarity of Central Kyzylkum phosphorite with phosphorite deposits in other North Africa and Afghanistan, some parts are different. Therefore, the method of production of products obtained from Central Kyzylkum phosphorite differs from the methods of traditional production. Central Kyzylkum phosphorite has some advantages over previously used Karatau phosphorite. It is a deficiency of four oxides of magnesium, iron, aluminum, and silicon
Keywords: Mineral fertilizers; Central Kyzylkum; phosphorites